On an Extensive Late Hydrologic Event in Gale Crater as Indicated by Water‐Rich Fracture Halos. Issue 12 (19th December 2022) - Gabriel, Travis S. J.; Hardgrove, Craig; Achilles, Cherie N.; Rampe, Elizabeth B.; Rapin, William N.; Nowicki, Suzanne; Czarnecki, Sean; Thompson, Lucy; Nikiforov, Sergei; Litvak, Maxim; Mitrofanov, Igor; Lisov, Denis; et al.
Abstract: We analyze spatially pervasive, light‐toned "halos" associated with fractures in a sedimentary unit (Stimson) of Gale crater, Mars, and report a similar network of halos discovered in a separate geologic group (Bradbury). Through a dedicated active neutron measurement campaign, we provide independent confirmation of the water‐rich nature of these features. Together with mineralogical and geochemical data, these features are consistent with abundant hydrated amorphous silica (opal‐A). We suggest that the mineral and amorphous assemblages are indicative of formation under low‐temperature and predominantly low‐pH conditions (passive silica enrichment) with minor contribution of silica (active silica enrichment) from adjacent units. We show that there is significant amorphous silica in the array of sedimentary rocks in Gale crater, allowing them to play a role in an active silica enrichment phase of halo formation. We suggest that the involved alteration event was short lived and our finding of vast halo networks in a distant, older unit implies a more vast network of hydrologic subsurface conduits than previously known. This relatively recent subsurface hydrologic system was present long after the transition from a warm and wet to a cold and dry Martian environment, extending the habitability conditions on Mars to an epoch that is generally considered not favorable for life on the surface. Finally, our bulk H quantification of these features, which ranges from ∼3–6 wt% H2 O‐equivalent‐H, suggests that the amorphous material in halos hosts ample supplies of readily released water, making them a considerable resource at the otherwise dry Martian equator. Plain Language Summary: Light‐toned opaline silica features found throughout rocks along Curiosity rover's traverse are the exposed roots of a vast fluid event in recent Martian geologic history. Using data collected from several instruments on Curiosity rover, we find evidence that the event was short lived and was followed by consistently cold and dry Mars climate conditions. This water‐rich subsurface network was shielded from modern harsh surface conditions, allowing for a potentially habitable environment on Mars in a more recent era. These light‐toned features are also ideal for follow‐up investigation or sample return as similar opal‐rich deposits on Earth are known to preserve traces of microbial life. Additionally, the features themselves contain a considerable amount of readily released water, making them an ideal resource at the otherwise dry Martian equator. Key Points: We demonstrate that water‐rich, opal‐A‐bearing light‐toned halos are more prevalent in Gale crater, Mars than previously understood Halos are associated with the conduits of a large‐scale hydrologic system in Gale crater Halos provided a subsurface habitable environment during a modern epoch of otherwise relatively uninhabitable surface conditions